The Magus of Freemasonry: The Mysterious Life of Elias Ashmole--Scientist, Alchemist, and Founder of the Royal Society - Churton, Tobias (Inner Traditions International, Limited, 2006)
Tobias Churton's portrait of Elias Ashmole (1617-1692) offers a perfect illustration of the true Renaissance figure--the magus. Ashmole was a key figure in the birth of modern science, a missing link between operative and symbolic Freemasonry, and a vital transmitter of esoteric thought when the laws of science were first taking hold.